Anthropology of disaster management - Narayan, S. (Sachindra) 1947-.; International Congress of Anthropological and Ethnological Sciences 1998 Williamsburg, Va.). (New Delhi Gyan Pub. House, 2000)
Contributed papers presented at the 14th International Congress of Anthropological and Ethnological Sciences, 26 July-1 August, 1998, at Williamsburg, Virginia, U.S.A.
Includes bibliographical references and index.
UPSA-1900g donated by Dr. Victor Paz
Keywords: Disasters -- Congresses; Emergency management -- Congresses; Emergency management -- India -- Congresses